Can a heart failure-specific cardiac rehabilitation program decrease hospitalizations and improve outcomes in high-risk patients? - Davidson, Patricia; Cockburn, J.; Newton, Phillip; Webster, J.; Betihavas, Vasiliki; Howes, L.; Owensby, D. (Sage Publications Ltd., 2010)
Background. Heart failure is a common and costly condition, particularly in the elderly. A range of models of interventions have shown the capacity to decrease hospitalizations and improve health-related outcomes. Potentially, cardiac rehabilitation models can also improve outcomes. Aim. To assess the impact of a nurse-coordinated multidisciplinary, cardiac rehabilitation program to decrease hospitalizations, increase functional capacity, and meet the needs of patients with heart failure. Method. In a randomized control trial, a total of 105 patients were recruited to the study. Patients in the intervention group received an individualized, multidisciplinary 12-week cardiac rehabilitation program, including an individualized exercise component tailored to functional ability and social circumstances. The control group received an information session provided by the cardiac rehabilitation coordinator and then follow-up care by either their cardiologist or general practitioner. This trial was stopped prematurely after the release of state-based guidelines and funding for heart failure programs.Results. During the study period, patients in the intervention group were less likely to have been admitted to hospital for any cause (44 vs. 69%, P = 0.01) or after a major acute coronary event (24 vs. 55%, P = 0.001). Participants in the intervention group were more likely to be alive at 12 months, (93 vs. 79%; P = 0.03) (odds ratio =3.85; 95% confidence interval = 1.0314.42; P = 0.0042). Quality of life scores improved at 3 months compared with baseline (intervention t = 4.37, P [ 0.0001; control t= 3.52, P [0.01). Improvement was also seen in 6-min walk times at 3 months compared with baseline in the intervention group (t = 3.40; P = 0.01). Conclusion. This study shows that a multidisciplinary heart failure cardiac rehabilitation program, including an individualized exercise component, coordinated by a specialist heart failure nurse can substantially reduce both all-cause and cardiovascular readmission rates, improve functional status at 3 months and exercise tolerance.